edited by
2,249 views
11 votes
11 votes
  1. Prove that powerset $(A \cap B) = \text{powerset}(A) \cap \text{powerset}(B)$
  2. Let $\text{sum} (n) = 0 + 1 + 2 + ..... + n$ for all natural numbers n. Give an induction proof to show that the following equation is true for all natural numbers $m$ and $n$:

$\text{sum}(m+n) = \text{sum}(m) + \text{sum}(n) + mn$

edited by

2 Answers

Best answer
13 votes
13 votes
For question (a):

To prove $P(A\cap B )= P(A)\cap P(B)$ we should show that $P(A\cap B )\subseteq P(A)\cap P(B)$ and $P(A)\cap P(B)\subseteq P(A\cap B )$.

For first part:

Lets take some subset $X\subseteq A\cap B$ then $X\in P(A\cap B )$. Also $X\subseteq A\wedge X\subseteq B$, means $X\in P(A)\wedge X\in P(B)$. Again this proves that $X\cap P(A)\cap P(B)$. This proves $P(A\cap B)\subseteq P(A)\cap P(B)\quad \to (1)$

For second part:

Take any $X$ such that $X\subseteq A$ and $X\subseteq B$. This is $X\in P(A)\wedge X\in P(B)$. That means $X\in P(A)\cap P(B)$. Now also $X\subseteq (A\cap B)$. This also means that $X\in P(A\cap B)$. This proves $P(A)\cap P(B)\subseteq P(A\cap B) \quad \to(2)$

From results (1) and (2),
$$P(A)\cap P(B)= P(A\cap B)$$
For question (b):

$\text{Sum}(n)=\frac{n(n+1)}{2}$

So, for $n=1\: \text{Sum}(1)=1$

For $n = 2, \text{Sum} (2) = 1 + 2 = 3$

$\text{Sum}(1+1) = \text{Sum}(1) + \text{Sum}(1) + 1\times 1 = 1+1+1=3$

So, base case of the formula holds true.
Lets assume the formula holds true for $n+m$

$\implies \text{Sum}(m+n)=\text{Sum}(m)+\text{Sum}(n)+mn$

$\qquad =\frac{m(m+1)}{2}+\frac{n(n+1)}{2}+mn$

$\qquad =\frac{(m+n)(m+n+1)}{2}$

Now, we get for
$\text{Sum}(m+n+1)= \frac{(m+n+1)(m+n+2)}{2}$
$\qquad =  \frac{(m+n)(m+n+2)}{2} +  \frac{(m+n+2)}{2}$
$\qquad  = \frac{(m+n)(m+n+1)}{2} +  \frac{(m+n+2)}{2} +\frac{m+n}{2}$
$\qquad = \frac{(m+n)(m+n+1)}{2} +  \frac{(m+n)}{2} + 1 +\frac{m+n}{2}$
$\qquad = \text{Sum}(m+n)+\text{Sum}(1) + (m+n) \times 1$

Hence, proved by mathematical induction.
edited by
0 votes
0 votes
proof by contradiction:

assume : P(A int B) != P(A) int P(B)

now,

A={1,2}

B={2,3}

P(A)={ empty set, {1}, {2}, {1,2} }

P(B)={ empty set, {3}, {2}, {3,2} }

A intersection B = {2}

P(A int B)={ empty set, {2} } = P(A) int P(B), which is contradicting our assumption.

therefore our assumption is wrong. hence the statement is proved.

Related questions

15 votes
15 votes
4 answers
2
Kathleen asked Sep 14, 2014
3,212 views
Consider the function $h: N \times N \rightarrow N$ so that $h(a,b) = (2a +1)2^b - 1$, where $N=\{0,1,2,3,\dots\}$ is the set of natural numbers.Prove that the function $...